Metode Penanggulangan Water ConingDari Beberapa Lapangan - M. Mahlil Nasution (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2022)
The problem of vertical movement of water infiltrates the productive layer. This is often referred to as Water Coning. This water coning problem can occur because the actual production rate exceeds the critical production rate (the production rate that is allowed by a well to be produced free of coning), so that excessive suction results in a flow pressure gradient exceeding the gravitational force resulting in a breakthrough of the productive layer by water. Symptoms of water coning can be seen from surface symptoms, namely a significant increase in water content. The study wells are suspected of having water coning, this can be seen from the graph of the increase in water content and time, so these wells are analyzed further. As a further stage of this research by analyzing how much coning has been formed and also analyzing the development of the coning. Then determine the handling system for the coning problem. The purpose of this study is to evaluate wells that are suspected of having water coning using research methods that have been reviewed in their critical rate analysis, to analyze the evaluation of wells experiencing water coning in order to determine the factors causing it and determine a system to overcome the water problem of the coning.